Construction of Self-Assembled Cartilage Tissue from Bone Marrow Mesenchymal Stem Cells Induced by Hypoxia Combined with GDF-5 - 田洪涛 张波 田青 刘勇 杨述华 邵增务 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
It is widely known that hypoxia can promote chondrogenesis of human bone marrow de- rived mesenchymal stem cells （hMSCs） in monolayer cultures. However, the direct impact of oxygen tension on hMSC differentiation in three-dimensional cultures is still unknown. This research was de- signed to observe the direct impact of oxygen tension on the ability of hMSCs to ＂self assemble＂ into tissue-engineered cartilage constructs, hMSCs were cultured in chondrogenic medium （CM） containing 100 ng/mL growth differentiation factor 5 （GDF-5） at 5% （hypoxia） and 21% （normoxia） 02 levels in monolayer cultures for 3 weeks. After differentiation, the cells were digested and employed in a self- assembly process to produce tissue-engineered constructs under hypoxic and normoxic conditions in vi- tro. The aggrecan and type ]I collagen expression, and type X collagen in the self-assembled con- structs were assessed by using immunofluorescent and immunochemical staining respectively. The methods of dimethylmethylene blue （DMMB）, hydroxyproline and PicoGreen were used to measure the total collagen content, glycosaminoglycan （GAG） content and the number of viable cells in each con- struct, respectively. The expression of type II collagen and aggrecan under hypoxic conditions was in- creased significantly as compared with that under normoxic conditions. In contrast, type X collagen expression was down-regulated in the hypoxic group. Moreover, the constructs in hypoxic group showed more significantly increased total collagen and GAG than in normoxic group, which were more close to those of the natural cartilage. These findings demonstrated that hypoxia enhanced chondro- genesis of in vitro, scaffold-free, tissue-engineered constructs generated using hMSCs induced by GDF-5. In hypoxic environments, the self-assembled constructs have a Thistological appearance and biochemical parameters similar to those of the natural cartilage.